S.T.O.N.E. Score in Prediction of Stone Clearance in PCNL - Raj K.c, Sudeep; Timilsina, Bhusan Raj; Kumar Kushwaha, Dipesh; Giri, Saroj (Journal of College of Medical Sciences-Nepal, 2023)
ABSTRACT Background S.T.O.N.E. score has been considered as standard scoring system for prediction of complication and to state the clearance of the stone. The objective of this research is to find out STONE score in predicting percutaneous nephrolithotomy (PCNL) success in stone free rate. Methods A cross sectional study was conducted in the department of urology in College of Medical Sciences and Teaching Hospital. Seventy five case of patient who underwent PCNL were included in the study and S.T.O.N.E. score was gathered like stone size, tract length (skin-to-stone distance), degree of obstruction (presence of hydronephrosis), number of involved calyces and stone essence (stone density). Collected data was entered and analyzed using SPSS. Results Among the total of 75 patients 40% (with 95% CI as 28.91% to 51.08%) had residual stone while remaining had no residual stone. 90.7% patients had 0-399 mm stone size, 97.3% had less than 100 mm tract length and likewise 29.3% had moderate to severe dilatation. Majority (68%) had 2-3 calyces involment and 72% had more than 950 HU stone density. Conclusion S.T.O.N.E. nephrolithometry is highly predictive of stone free status in patients undergoing PCNL and provides a quick, easy-to-apply method for grading the complexity of PCNL